2015
DOI: 10.1080/10511482.2015.1060249
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Homelessness Among Families and Single Adults After Exit From Homelessness Prevention and Rapid Re-Housing Programs: Evidence From the Department of Veterans Affairs Supportive Services for Veteran Families Program

Abstract: This article assesses the extent and predictors of homelessness among Veterans(both Veterans in families with children and single adults Veterans) exiting the Supportive Services for Veteran Families (SSVF) program, which is a nationwide homelessness prevention and rapid re-housing program geared primarily towards those experiencing crisis homelessness. Among rapid rehousing participants, 16% and 26% of single adult Veterans experienced an episode of homelessness at one and two years post-SSVF exit; the compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…The percentage of HPRP veterans returning to homeless services (20.0%) was comparable to the national study of SSVF in which 17.9% to 26.6% of SSVF veteran recipients returned to VA homeless services (Byrne et al, 2016). Prior research has demonstrated few demographic or psychosocial differences between homeless veterans and other single homeless adults residing in shelters (Petrovich, Pollio, & North, 2014) and formerly homeless adults in supported housing (Tsai, Mares, & Rosenheck, 2012 There is limited research comparing service needs and housing outcomes between veterans and non-veterans experiencing homelessness.…”
Section: Discussionsupporting
confidence: 54%
“…The percentage of HPRP veterans returning to homeless services (20.0%) was comparable to the national study of SSVF in which 17.9% to 26.6% of SSVF veteran recipients returned to VA homeless services (Byrne et al, 2016). Prior research has demonstrated few demographic or psychosocial differences between homeless veterans and other single homeless adults residing in shelters (Petrovich, Pollio, & North, 2014) and formerly homeless adults in supported housing (Tsai, Mares, & Rosenheck, 2012 There is limited research comparing service needs and housing outcomes between veterans and non-veterans experiencing homelessness.…”
Section: Discussionsupporting
confidence: 54%
“…Use of the VA's continuum of homelessness programs is not well understood, including whether differences exist between single and multiple program users and whether there are patterns in the timing and duration by which different VA homelessness programs are used. Prior research, often cross-sectional studies, has examined the characteristics, service use, and housing outcomes of veterans participating in individual VA homelessness programs (5,7,8). However, examining participation in these programs in isolation ignores the fact that veterans are likely to be eligible for (and may access) multiple programs over time.…”
Section: Highlightsmentioning
confidence: 99%
“…The Housing First model (e.g., Tsemberis et al) has discussed why having a place to call home is simply better. A large part of the argument is that it allows individuals to address the underlying issues that brought them into homelessness to begin with, whether it is unemployment, mental illness, substance abuse, or something else [ 26 , 27 , 28 ]. This study is a contribution toward understanding why having a home is better.…”
Section: Resultsmentioning
confidence: 99%
“…Public health literature has emphasized the importance of the social determinants of health including a number of measures of quality of life and well-being [ 9 ]. The Housing First model has supported the idea that, when people are housed, they can address the underlying issues, including substance abuse, physical issues, and health issues [ 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation